2019
DOI: 10.1016/j.heliyon.2019.e01466
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol (PEG) decorated graphene oxide nanosheets for controlled release curcumin delivery

Abstract: Nowadays, the use of nanostructures in various medical and biological fields such as drug delivery in cancer treatment is increasing. Among the nanostructures, graphene oxide (GO) is an excellent candidate for drug delivery application because of its unique properties. For more stability, GO can bind with various polymers by its carboxyl, hydroxyl and epoxy functional groups. In this study, firstly GO synthesized by the improved Hummers chemical method and then polyethylene glycol polymer was conjugated to it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 26 publications
(27 reference statements)
8
44
0
1
Order By: Relevance
“…The polar groups are usually further modified by functionalization with the biocompatible and hydrophilic polymers, such as polyethylene glycole (PEG) or polyvinylpyrrolidone (PVP), then different drugs are loaded on the GR plane. Among GBMs, GO is an excellent material for DDSs, precisely because the presence of functional groups makes it easy to modify its surface [12,26].…”
Section: Graphene-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polar groups are usually further modified by functionalization with the biocompatible and hydrophilic polymers, such as polyethylene glycole (PEG) or polyvinylpyrrolidone (PVP), then different drugs are loaded on the GR plane. Among GBMs, GO is an excellent material for DDSs, precisely because the presence of functional groups makes it easy to modify its surface [12,26].…”
Section: Graphene-based Materialsmentioning
confidence: 99%
“…PEGylated GO, loaded with curcumin, as an anticancer drug, proved to be an excellent controlled-release DDS for the delivery of curcumin [26]. The conjugation of PEG-PLGA, GO, and folic acid (FA) with DOX, via a disulfide bond, provids a NC with enhanced stability under physiological conditions and DOX liberation in the reductive environment of cancer cells.…”
Section: Figure 11mentioning
confidence: 99%
“…It can be found that three distinct characteristic absorption peaks on GO curve appeared at 3400, 1624, and 1114 cm −1 , respectively, which corresponded to the groups of OH, C O, and C O. 25,26 In the FTIR curve of GO-IPEG, the CH 2 absorption peak at 2880 cm −1 , the CH in-plane bending vibration peak at 1458 cm −1 , as well as the absorption peaks at 1724, 1240, and 1100 cm −1 , are due to the stretching vibrational peaks of ester 27,28 The results indicated that the esterification reaction has been occurred successfully between IPEG and GO. As for the GO-PCE spectrum curve, the peaks at 2880, 1740, and 1110 cm −1 correspond to CH 2 stretching vibrational peaks, C O group on AA structure and C O C group on IPEG structure, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…The molecular structure of GO, GO‐IPEG, and GO‐PCE was characterized by FTIR spectrum, as shown in Figure . It can be found that three distinct characteristic absorption peaks on GO curve appeared at 3400, 1624, and 1114 cm −1 , respectively, which corresponded to the groups of OH, CO, and CO . In the FTIR curve of GO‐IPEG, the CH 2 absorption peak at 2880 cm −1 , the CH in‐plane bending vibration peak at 1458 cm −1 , as well as the absorption peaks at 1724, 1240, and 1100 cm −1 , are due to the stretching vibrational peaks of ester groups (CO and COC) in the molecular structure of GO‐IPEG .…”
Section: Resultsmentioning
confidence: 97%
“…GO-PF68 (GP) was developed via the covalent linkage of the carboxyl functional groups on the surface of GO and the hydroxyl groups of PF68 through the EDC/NHS crosslinking reaction. [34][35][36][37] First, 420 mg of PF68, 20 mg of EDC Á HCl, and 20 mg of NHS were dissolved completely in 10 mL of 0.1 mol/L of phosphate buffer (PB, pH 5.0), and the solution was activated for 30 min with ultrasound. Next, the solution was dripped into 40 mL of GO aqueous dispersion (1 mg/mL), followed by 24 h of magnetic stirring.…”
Section: Synthesis Of Tf/fa-go-pf68mentioning
confidence: 99%